Carbon dots: An innovative luminescent nanomaterial: Photovoltaics: Special Issue Dedicated to Professor Yongfang Li. Issue 3 (6th August 2021) - Shi, Yuxin; Xu, Huimin; Yuan, Ting; Meng, Ting; Wu, Hao; Chang, Jianqiao; Wang, Haoyu; Song, Xianzhi; Li, Yunchao; Li, Xiaohong; Zhang, Yang; Xie, Wenjing; et al.
Abstract: In recent years, carbon dots (CDs), including carbon nanodots, carbonized polymer dots, carbon quantum dots, and graphene quantum dots have attracted a mounting interest as readily accessible, nontoxic, and relatively inexpensive carbon‐based nanomaterials. Yet, despite intense research for a number of years, a unifying picture is still lacking to clarify the exact definition, clear chemical structure, and unique optical properties of this family of nanomaterials. In this review, we systematically summarize the recent development of CDs from molecular design to related properties of excited states as well as their applications in optoelectronic devices and biology. We point out the current challenges, including exploring precise synthesis, clarifying the structure‐property relationship, and regulating singlet and triplet states of fluorescence, phosphorescence, and delayed fluorescence. Moreover, the structural optimization of optoelectronic devices, tumor targeting mechanism, selective imaging, and drug delivery of CDs are also highlighted. We hope that the information provided in this review will inspire more exciting research on CDs from a brand‐new perspective and promote practical application of CDs in multiple directions of current and future research. Abstract : As a new type of luminescent carbon‐based nanomaterials, carbon dots (CDs) have attracted a mounting interest due to their low toxicity, great solution‐processability, ease of synthesis, and tunable photoluminescence. Here, we systematically summarize the recent development of CDs from structural design to related properties of excited states as well as their applications in optoelectronic devices and biology.